O laboratório de tecnologias intelectuais - LTi na perspectiva da competência informacional: os múltiplos olhares da Ciência da Informação - Rodrigues, Thamyres Ferreira (2017)
Learning can occur in a variety of environments and one of them is virtual, including social media sources, blogs and websites. It’s in this perspective, that we present the Networks Project of the Outlab of Intellectual Technologies - LTi, which has the proposal to deepen the studies of the scientific field of Information Science, while considering the importance of learning networks, according to the regime and mediation of information, with the help of the information literacy applied in the Portal of the LTi, while not understanding social action as a way of life. For this reason, we seek to explore what informational skills we can indicate in the Portal of the LTi. We aim to analyze the Portal, within the scope of the information literacy, identifying the elements of the information regime of the Lti; comparing the standards and frameworks of the information literacy of the devices and artifacts and also describing the information literacy of the LTi Portal. For this purpose, we used the methods of documentary research in a virtual environment, based on a qualitative, exploratory and descriptive nature. Data collection was made on the LTi website, organized into categories of information skills, according to the Standards and Information Competency Framework for Higher Education, proposed by the Association of College and Research Libraries. It was concluded that the frameworks can cover more informational skills, providing more benefits to students and users regarding the standards of competence. We recommend an epistemological deepening of the information regime and competency models based on the framework, since this structure is more complete and applicable. Also that the informational skills which are the following: to identify, to access, to search, to evaluate, to organize and to use are promoted by teachers, librarians and all information professionals to their students and users so that they develop increasingly advanced innovative informational services and products.